Star and National Myths in Cold War Allegories: Marlene Dietrich’s Star Persona and the Western in Fritz Lang’s Rancho Notorious (1952) - Hilaria Loyo (European Journal of American Studies)
Fritz Lang’s film Rancho Notorious offered Lang himself the chance to direct a western in which he could develop a double focus, contrasting indigenous American against foreign influences. He was helped in this by Marlene Dietrich, who had begun her career as a symbol of modernization and consumer culture. Lang used Dietrich in the film to comment on aspects of modernity and, at the same time, to offer an allegorical reading of American nationalism of the McCarthy era. Through Dietrich’s character, Altar, the boss of the Chuck-a-Luck ranch and the criminal world it embodied, Lang critiqued the emerging Cold War ideology of the man as patriarchal figure and bread-winner. At the same time, by moving Dietrich progressively towards the centre of the film, he produced an amalgam of the women’s film and the Western genre that suggested the pointlessness of the male aggression the Western itself had traditionally embodied.